2019
DOI: 10.1177/1078155219840796
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for survival in patients with mucosal and ocular melanoma treated with ipilimumab: Turkish Oncology Group study

Abstract: Objective To evaluate prognostic factors associated with the use of ipilimumab in patients with mucosal and uveal melanoma. Methods In this multicenter, retrospective study, 31 patients with uveal and mucosal melanoma diagnosed between 2010 and 2017 were enrolled. Patients’ characteristics, metastatic disease sites, treatment before ipilimumab therapy, performance status, hemoglobin, lactate dehydrogenase levels, B-RAF and c-kit mutation status, toxicity, and survival data were assessed for patients with mucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Ipilimumab was assessed in 13 studies with a total of 303 patients (Table 1). 1729 A pooled analysis of 36 patients with MM treated with ipilimumab monotherapy showed efficacy with an ORR of 23.3% and median PFS of 3.0 months. 17 DeCOG was an open-label, multi-center, single-arm phase II study that included patients with melanoma irrespective of the primary melanoma location.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ipilimumab was assessed in 13 studies with a total of 303 patients (Table 1). 1729 A pooled analysis of 36 patients with MM treated with ipilimumab monotherapy showed efficacy with an ORR of 23.3% and median PFS of 3.0 months. 17 DeCOG was an open-label, multi-center, single-arm phase II study that included patients with melanoma irrespective of the primary melanoma location.…”
Section: Resultsmentioning
confidence: 99%
“…23 In a multicenter, retrospective analysis of 33 patients with unresectable or metastatic MM treated with ipilimumab at a dose of 3 or 10 mg/kg, one immune-related CR, one immune-related PR, six immune-related stable disease, and 22 immune-related progressive disease cases were observed at approximately 12 weeks after initiation of therapy. 24 A multicenter retrospective study included 11 patients with MM receiving ipilimumab at seven different medical oncology departments in Turkey and the median OS was 6.9 months (95% CI 25 A single-center, prospective cohort analyzed 24 patients with unresectable locally advanced or metastatic MM who received ipilimumab. 26 The ORR was 8.2% with a median PFS of 5 months (95% CI 2.6-33.1) and a median OS of 16.2 months (95% CI 5.3-42.6).…”
Section: Anti-ctla-4 Monoclonal Antibodiesmentioning
confidence: 99%
“…Since 2013, 12 studies with 6-76 patients with MM treated with ipilimumab were reported (Table 2). [70][71][72][73][74][75][76][77][78][79][80][81] As for prospective trials, a pooled analysis of CheckMate 067 and CheckMate 069 trials including 36 MM patients demonstrated a poor ORR of 8.3% and a median PFS of 2.7 months. 76 Another multi-center, single-arm phase II prospective study conducted in Germany reported an ORR of 17% and a median OS of 9.6 months with 1-year OS rate of 14% in 6 patients with MM.…”
Section: Anti-ctla-4 Antibodymentioning
confidence: 99%
“…Because of this success ipilimumab has been tested in patients with UM. In a retrospective analysis of 11 patients with mucosal melanoma and 20 with UM, the median OS after ipilimumab treatment was found to be 5 [131]. The efficacy and tolerability of ipilimumab was also assessed retrospectively in an Australian clinical setting with 104 melanoma patients who were followed over a median period of 7 months [132].…”
Section: (B) Cancer Immunotherapymentioning
confidence: 99%
“…In a retrospective analysis of 11 patients with mucosal melanoma and 20 with UM, the median OS after ipilimumab treatment was found to be five months in the UM group (95% CI 1–17 months). This study suggested that ipilimumab may have benefits as a first/second line treatment over alternate treatments (median OS of 12.3 months; 95% CI 3.8–20.8 months for ipilimumab, compared to 3.3 months; 95% CI 0–8.4 months for other treatments) [129]. The efficacy and tolerability of ipilimumab was also assessed retrospectively in an Australian clinical setting with 104 melanoma patients who were followed over a median period of seven months [130].…”
Section: Evaluation Of Drug Treatments For Primary and Metastatic Ummentioning
confidence: 99%